QuantiFERON-Cytomegalovirus Assay for Prediction of Cytomegalovirus Viremia in Kidney Transplant Recipients: Study From High Cytomegalovirus Seroprevalence Country - Pongsakornkullachart, Kritsada; Chayakulkeeree, Methee; Vongwiwatana, Attapong; Kantakamalakul, Wannee; Skulratanasak, Peenida; Phoompoung, Pakpoom (Frontiers in cellular and infection microbiology, 2022)
Early studies showed the utility of pretransplant QuantiFERON-Cytomegalovirus (QF-CMV) assays for CMV-disease prediction post kidney transplant (KT). However, recent data are conflicting. This prospective cohort study enrolled adult patients undergoing KT between July 2017 and May 2019. Patients with antithymocyte globulin therapy or negative pretransplant CMV IgG were excluded. QF-CMV assays were performed on transplantation day and one month thereafter, and CMV viral loads were obtained 1, 3, and 6 months posttransplantation. The primary outcome was CMV viremia within 6 months. The QF-CMV assay-posttransplant CMV viremia association was analyzed. Fifty-five patients were enrolled (male, 58.2%; mean (SD) age, 46.5 (10.2) years). Fifty-two (94.5%) received CMV-seropositive donor kidneys. Over 6 months, 29 patients developed CMV viremia (52.7%), with 14 (25.5%) having significant viremia requiring antiviral therapy. The CMV-viremia incidence of patients with nonreactive and reactive baseline QF-CMV assays did not differ significantly (55.3% and 47.1%; = 0.573). Among patients with reactive pretransplant QF-CMV assays, there was a trend toward a lower incidence of CMV viremia for those who were persistently reactive at 1 month after KTs, although there was no statistically significant difference (50% vs 83%; = 0.132). Our study could not support the use of single-timepoint pretransplant or 1-month posttransplant QF-CMV assays as a predictor for posttransplant CMV viremia in CMV seropositive KT recipients. Investigation of the association between dynamic QF-CMV-status changes and CMV-viremia incidence are needed.